Development of Pictorial Riddle-Based Guided Inquiry Model Learning Devices to Improve Students' Problem Solving Ability - Irfan; Joni Rokhmat; Ni Nyoman Sri Putu Verawati (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2023)
This research is in the form of development which aims to produce products in the form of pictorial riddle-based guided inquiry learning tools that are valid, practical, and effective to improve students' problem-solving abilities. The flow of development research stages uses a 4D model consisting of defining, designing, developing, and disseminating. The products developed are Learning Implementation Plans, Teaching Materials, Student Worksheets, Learning Media, and problem-solving ability test instruments. Data collection techniques were carried out through the validation of learning tools by validators, student response questionnaires, observation sheets of learning implementation, and test instruments. The results of the validation of learning tools reach an average validity value of 79.347% with valid criteria. The students' responses obtained a score of > 80% with good criteria and the average learning implementation for three meetings was 3.5 with good criteria. The effectiveness of the developed learning tools can be analyzed by calculating the t-test. Based on calculations using the t-test, the results obtained are tcount > ttable, namely 17.270 > 1.729. The results of the N-gain calculation of students' problem-solving abilities are 0.6075 with moderate criteria. Based on the results of this study, it can be concluded that the guided inquiry learning model based on pictorial riddles to improve students' problem-solving abilities is valid, practical, and effective in learning.   Keywords: Guided inquiry models, pictorial riddles, problem solving abilities.